Correction: Biofunctionalized pectin hydrogels as 3D cellular microenvironments. Issue 42 (2nd October 2015) - Neves, Sara C.; Gomes, David B.; Sousa, Aureliana; Bidarra, Sílvia J.; Petrini, Paola; Moroni, Lorenzo; Barrias, Cristina C.; Granja, Pedro L.
Abstract : Correction for 'Biofunctionalized pectin hydrogels as 3D cellular microenvironments' by Sara C. Neves et al., J. Mater. Chem. B, 2015, 3, 2096–2108.